A Polysaccharide Isolated from Dictyophora indusiata Promotes Recovery from Antibiotic-Driven Intestinal Dysbiosis and Improves Gut Epithelial Barrier Function in a Mouse Model - Kanwal, Sadia; Joseph, Thomson Patrick; Owusu, Lawrence; Xiaomeng, Ren; Meiqi, Li; Yi, Xin (Nutrients, 2018)
Despite the tremendous biological activity of polysaccharides from the mushroom Dictyophora indusiata, its role in the restoration of gut microbiota has not yet been explored. The present study aimed to investigate whether D. indusiata polysaccharide (DIP) could modulate the recovery of gut microbiota composition and intestinal barrier function after broad-spectrum antibiotic-driven dysbiosis. Alteration and restoration in the microbial communities were elucidated by the Illumina MiSeq platform. Colon histology, expression of tight-junction associated proteins, and serum/tissue endotoxin and cytokine levels were evaluated. Two-week daily oral administration of clindamycin and metronidazole resulted in reduced bacterial diversity and richness, and perturbed the microbial flora at various taxonomic levels (altered Firmicutes/Bacteroidetes ratio and increased relative abundance of harmful flora (Proteobacteria, Enterococcus, and Bacteroides)), whereas DIP administration reversed the dysbiosis and increased beneficial flora, including Lactobacillaceae (lactic acid-producing bacteria), and Ruminococaceae (butyrate-producing bacteria). In addition, it resulted in the reduction of endotoxemia (through lipopolysaccharides (LPSs)) and pro-inflammatory cytokine (tumor necrosis factor alpha (TNF-α), interleukin 6 (IL-6), and interleukin 1β (IL-1β)) levels, with the increased expression of tight-junction associated proteins (claudin-1, occludin, and zonula occludens-1). These findings not only suggested a comprehensive understanding of the protective effects of a DIP in the restoration of gut microbiota but also highlighted its role in the enhancement of gut barrier integrity, reduction of inflammation and lowering of endotoxin levels in mice.